CONSTRUCTION DESIGN AND DRIVE SYSTEM ON PLASTIC BOLT PRINTING MACHINE WITH MSME SCALE (DINAMIS, 2023)
Plastic screw molding machine is one of the important equipment in the manufacturing industry, including micro, small and medium scale (MSMEs). The purpose of this research is to design an efficient and reliable construction and drive system for plastic screw molding machines with MSME scale. This research involved a literature study on printing presses, needs analysis, conceptual design, simulation analysis, prototyping, testing, evaluation, and improvement. Printing machines or molding machines are usually used in large companies, therefore the author intends to make the design and design of printing machines or molding machines simple and can be used by the public at an affordable price. Plastic pellets of the LLDPE type are used for testing the manufacture of plastic bolts using a plastic bolt molding machine that has been designed and made by the author. In this research method the author only discusses component calculations, namely electric motor calculations, pulley calculations, peg calculations, v-belt calculations, and load calculations on the frame. The working system of this plastic bolt molding machine is that first the band heater is turned on first, then the electric motor system is turned on, and after that the LLDPE plastic pellets are put into the container. The plastic pellets will be pushed using a screw which is driven by an electric motor and heated using a band heater, after which the molten plastic pellets come out and immediately enter the mold or molding. In the results of the first test using a temperature of 80 o C and spending 4.36 minutes in a plastic bolt, in the second test using a temperature of 150 o C and spending 2.50 minutes in a plastic screw, and in the third test using a temperature 120 o C and spent 3.30 minutes in one plastic screw.